2020
DOI: 10.1371/journal.pone.0228580
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anaesthetic technique, clinicopathological characteristics and the magnitude of the postoperative systemic inflammatory response in patients undergoing elective surgery for colon cancer

Abstract: Background/aimThe magnitude of the postoperative systemic inflammatory response (SIR) is now recognised to be associated with both short and long-term outcomes in patients undergoing surgery for colon cancer. During such surgery, it is unclear whether the anaesthetic regimens influence the magnitude of the postoperative SIR, independent of other factors. The aim of the present study was to examine the association between anaesthetic agents, clinicopathological characteristics and the magnitude of the postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Regional anaesthesia is reported to suppresses the incidence of postoperative complications after gastrointestinal surgery. 26,27 Beta-blocker therapy is also thought to protect against major complications after gastrointestinal surgery. 28,29 As regional anaesthesia impedes the neural transmission from the periphery to the central nervous system, it might play a role in reducing the nociceptive response index during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional anaesthesia is reported to suppresses the incidence of postoperative complications after gastrointestinal surgery. 26,27 Beta-blocker therapy is also thought to protect against major complications after gastrointestinal surgery. 28,29 As regional anaesthesia impedes the neural transmission from the periphery to the central nervous system, it might play a role in reducing the nociceptive response index during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regional anaesthesia is reported to suppresses the incidence of postoperative complications after gastrointestinal surgery 26,27 . Beta-blocker therapy is also thought to protect against major complications after gastrointestinal surgery 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Furthermore, these authors, in a retrospective audit of the effect of anesthetic technique on the magnitude of the postoperative CRP in patients undergoing elective open or laparoscopic surgery for colon cancer, reported that the magnitude of the postoperative SIR in particular, POD 2 CRP, was modulated by the induction of RA in patients who underwent open surgery, but not laparoscopic surgery for colorectal cancer. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%